PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK KELAS X MIA SMA SANTO PAULUS MANOKWARI PADA MATERI SISTEM PERIODIK UNSUR - Irdawati Irdawati (Universitas Papua, Manokwari, Indonesia, 2021)
AbstactThe implementation of 2013 curriculum for Senior High Schools (SMA) in Manokwari has not been fully implemented in schools. This is due to a lack of understanding in the implementation process both in planning, implementation and assessment. The 2013 curriculum emphasizes the activeness of students and teachers as facilitators. One of the efforts that can be made so that in the process of learning activities students become the center and play an active role in learning activities is to implement a learning model based on the 2013 curriculum, namely Discovery Learning. This study aims to determine the significant difference from the use of the model Discovery Learning to the cognitive learning outcomes of class X MIA students of SMA Santo Paulus Manokwari on the elemental periodic system material. The research method used is Pre-Experimental Designs with the form of One-Group Pretest-Posttest Design. The sampling technique used saturated sampling with a sample size of 15 people. The instrument used in measuring the test of students' cognitive learning outcomes is a multiple choice test. Based on the results of data processing obtained, the averagescore pretest was 41.33 and the averagescore was posttest 78.67, the standard results obtained were Gain which showed an increase in the learning ability of students before being given treatment and after being given treatment of 0.77. Based on the Paired Sample T-test, it was found that there was an effect of the use of the learning model Discovery Learning on the cognitive learning outcomes of students in class X MIA SMA Santo Paulus Manokwari on the element periodic system material with a large influence of 64% Keywords: learning model, discovery learning, cognitive learning outcomes, elemental periodic system material, SMA Santo Paulus Manokwari